Unveiling ferroptosis: a new frontier in skin disease research - Wang, Ke; Lin, Yumeng; Zhou, Dan; Li, Peipei; Zhao, Xiaoying; Han, Zhongyu; Chen, Haoran (Frontiers in Immunology, 2024)
Ferroptosis, a form of regulated cell death distinct from apoptosis, necrosis, and autophagy, is increasingly recognized for its role in skin disease pathology. Characterized by iron accumulation and lipid peroxidation, ferroptosis has been implicated in the progression of various skin conditions, including psoriasis, photosensitive dermatitis, and melanoma. This review provides an in-depth analysis of the molecular mechanisms underlying ferroptosis and compares its cellular effects with other forms of cell death in the context of skin health and disease. We systematically examine the role of ferroptosis in five specific skin diseases, including ichthyosis, psoriasis, polymorphous light eruption (PMLE), vitiligo, and melanoma, detailing its influence on disease pathogenesis and progression. Moreover, we explore the current clinical landscape of ferroptosis-targeted therapies, discussing their potential in managing and treating skin diseases. Our aim is to shed light on the therapeutic potential of modulating ferroptosis in skin disease research and practice.